Antimicrobial potential of vapour phase propionic acid against Salmonella typhimurium contaminated on Cherry tomato (Solanum lycopersicum var. cerasiforme) - Sundarasukha, K.; Laopaisanwanithsiri, S.; Tepsorn, R. (International Journal of Agricultural Technology, 2020)
Salmonella sp. is increasingly recognized as significant cause of foodborne illness. Several decontamination procedures have been applied to reduce the number of this organism. The potential of mechanically vapourized propionic acid solution (MVP) on the reduction of S. typhimurium contaminated on on Cherry tomato (Solanum lycopersicum var. cerasiforme) was reported. In vitro surface inhibition at low population and high population were shown. MVP at the concentration of 70.0% demonstrated the completely inhibition within 15 min at 4°C. At the concentration of 70.0% the absolutely inactivated and observed within 5 min at 50°C. For the evaluation of antimicrobial activity of MVP over time, the results indicated that ca. 8.00 Log10 CFU/ml reduction were found within 5, 10, 15, 20, 25 and 30 min at the concentration at 5.0%, 10.0%, 30.0%, 60.0% and 70.0%, respectively. The effectiveness of MVP increased when the temperature of MPV process increased. The reduction of S. typhimurium contaminated on Cherry tomato using MPV was expressed. The effectiveness of MVP on the reduction of S. typhimurium depended on the concentration of propionic acid solution, the fumigation time and temperature. The biological and physical changes of Cherry tomato during 15 days of storage at room temperature and 4°C after fumigated demonstrated that MPV at concentration of 70.0% for 5 min at 50°C and 4°C vapourized in 70.0% for 15 min, indicated that the completely inhibition of S. typhimurium contaminated Cherry tomato was accomplished. Moreover, the colour and physical appearance of fumigated Cherry tomato was not different from fresh and the control. The propionic acid in vapour phase demonstrated the antimicrobial potential against S. typhimurium at both after fumigation process and storage time.